Free Hand Insertion Technique of S2 Sacral Alar-Iliac Screws for Spino-Pelvic Fixation: Technical Note, Acadaveric Study - Park, Jong-Hwa (J Korean Neurosurg Soc, 2015)
A rigid spino-pelvic fixation to anchor long constructs is crucial to maintain the stability of long fusion in spinal deformity surgery. Besides obtaining immediate stability and proper biomechanical strength of constructs, the S2 alar-iliac (S2AI) screws have some more advantages. Four Korean fresh-frozen human cadavers were procured. Free hand S2AI screw placement is performed using anatomic landmarks. The starting point of the S2AI screw is located at the midpoint between the S1 and S2 foramen and 2 mm medial to the lateral sacral crest. Gearshift was advanced from the desired starting point toward the sacro-iliac joint directing approximately 20° angulation caudally in sagittal plane and 30° angulation horizontally in the coronal plane connecting the posterior superior iliac spine (PSIS). We made a S2AI screw trajectory through the cancellous channel using the gearshift. We measured caudal angle in the sagittal plane and horizontal angle in the coronal plane. A total of eight S2AI screws were inserted in four cadavers. All screws inserted into the iliac crest were evaluated by C-arm and naked eye examination by two spine surgeons. Among 8 S2AI screws, all screws were accurately placed (100%). The average caudal angle in the sagittal plane was 17.3±5.4°. The average horizontal angle in the coronal plane connecting the PSIS was 32.0±1.8°. The placement of S2AI screws using the free hand technique without any radiographic guidance appears to an acceptable method of insertion without more radiation or time consuming.